The Importance of Carthaginian Military Operations in Sicily Through Ancient Sources - NOUREDDINE , Karima (The Algerian Historical Journal, 2026)
Some historians attribute Carthage’s reluctance to engage in military action in Sicily to its preoccupation with suppressing some revolts in Africa, which were caused by Carthage’s weak taxation of the natives to cover the needs of war. The divergence of interests was also behind the differences in the position that had to be taken in Sicily. Hanno and his supporters from the ruling oligarchy leaned towards peace and opposed the policy of the Barcid family, since these merchants viewed state and social affairs only through the lens of their economic interests and what they could gain from them. They considered the continued presence of Carthaginian armies in Sicily a burden on the state treasury. Therefore, Hanno believed it preferable to concentrate efforts in African territories. On the other hand, the advocates of war, led by Hamilcar Barca, saw the necessity of holding on to Drepanum and Lilybaeum, from where uprisings should be stirred among Rome’s subject peoples to weaken its power, because without this Carthage could never find peace.